Fuzzy analytic hierarchy process approach: Uncover the motivating gamification elements for massive open online courses (MOOCS) - Ling, Nie Hui (Universiti Malaysia Sarawak (UNIMAS), 2017)
The evolution of education in this digital age has made educational technology especially distance education to be tremendously prevalent. From this perspective, Massive Open Online Courses (MOOCs) have arisen as popular trend in educational technology. Yet, many studies found that this new trend of education delivery has shown outlandishly low retention rate. Accordingly, there are large-scale of studies have conducted to examine the reason of this occurrence but most of the researchers have overlooked the motivational affordances which are one of the main contributions to the learner retention rate in distance learning. This study intends to uncover the motivating gamification elements for MOOCs by assessing four different ARCS dimensions which namely as Attention, Relevance, Confidence and Satisfaction. Fuzzy Analytic Hierarchy Process Approach (FAHP) was implemented as the methodology of this study. This study conducted with 120 participants.